Penggunaan Kartu Bilangan Sebagai Media Pembelajaran Untuk Meningkatkan Hasil Belajar Matematika Kelas I SD Negeri 001 Rambah Hilir - Ermiati Ermiati (Indonesian Journal of Basic Education, 2018)
Abstract, The subjects of this study are the students of class I B SD Negeri 1 which amounted to 29 students. Action research is carried out in 2 cycles. Data collection in this study using test and observation methods. The result data of the research on the addition and reduction material were analyzed by quantitative descriptive. The results showed that learning by using the number card media can improve the learning outcomes of mathematics in addition and reduction in class I SD Negeri 1, which in the initial condition of the results before the action was given an average value of 5.58. In cycle I using the number card media an increase so that the average value of the class to 6.37. In cycle II showed an increase with the average obtained by 7.47